Association of platelet activation markers with cancer-associated venous thromboembolism. (2nd January 2016) - Riedl, Julia; Hell, Lena; Kaider, Alexandra; Koder, Silvia; Marosi, Christine; Zielinski, Christoph; Panzer, Simon; Pabinger, Ingrid; Ay, Cihan
Abstract: Venous thromboembolism (VTE) is a frequent complication in cancer patients. Platelet activation is thought to be involved in cancer-associated VTE. Here, we determined the association between evolving markers of platelet activation (soluble P-selectin [sP-selectin], soluble CD40 ligand [sCD40L], thrombospondin-1 [TSP-1] and platelet factor-4 [PF-4]) and the development of cancer-associated VTE. A nested matched case–control study was applied within a cohort of 1779 patients with different types of cancer that had been included in the Vienna Cancer and Thrombosis Study (CATS), a prospective, observational study on patients with newly diagnosed or progressive cancer after remission. Primary endpoint is symptomatic VTE during a maximum follow-up of 2 years. Cases (patients who developed VTE during follow-up) were matched in a 1:2 ratio to controls without VTE during follow-up with respect to tumor type, stage and time of observation in the study. In total, 131 VTE cases were compared to 262 controls. In logistic regression analysis, only sP-selectin was associated with risk of VTE. The odds ratios (OR) per double increase of sP-selectin, sCD40L, TSP-1 and PF-4 were 1.66 (95% confidence interval: 1.17–2.35, p = 0.005), 1.04 (0.89–1.21, p = 0.635), 1.09 (0.90–1.32, p = 0.360) and 1.03 (0.87–1.21, p = 0.737), respectively. In conclusion, sP-selectin, but not sCD40L, TSP-1 or PF-4 were associated with risk of VTE in cancer patients in this nested case–control study.